Advertising literacy training: The immediate versus delayed effects on children's responses to product placement. (14th November 2017) - De Jans, Steffi; Hudders, Liselot; Cauberghe, Veroline
Abstract : Purpose: This paper aims to examine the immediate and delayed effects of advertising literacy training on children's cognitive advertising literacy for an embedded advertising format, product placement and, subsequently, its persuasive effects. In addition, this study explored whether this effect is moderated by children's general advertising liking. The study also investigated whether the effects of training were dependent on children's ages. Design/methodology/approach: The present study is conducted using a three (training session: control condition vs advertising literacy training with immediate ad exposure vs advertising literacy training with ad exposure after one week) by two (age: 7-8 years vs 10-11 years) between-subjects experimental design. Findings: The results of the experimental study showed that advertising literacy training increases children's cognitive advertising literacy for product placement for both younger and older children and both immediately and delayed (measured after one week). In addition, cognitive advertising literacy had an influence on the effectiveness of product placement (i.e. purchase request) when children's general ad liking was low, though not when it was high. No moderating effects of age were found. Practical implications: This study shows that advertising literacy training sessions can improve children's cognitive advertising literacy for non-traditional, embedded advertising formats. Originality/value: This study is one of the first to examine and confirm the immediate and delayed effects of advertising literacy training sessions on children's cognitive advertising literacy for non-traditional advertising formats.